Il sistema mantico ittita KIN - Warbinek, Livio (Premio Ricerca «Città di Firenze», 2020)
The present dissertation is concerned with the KIN oracle, a symbolic divination technique produced by the Hittite in the 2nd mill. B.C. and developed only in the Hittite cultural milieu. Like other omens of the Ancient Near East, the Hittite oracles were considered to be messages from the gods. The Hittite solicited omens included Extispicy, Augury, the Bed Oracle, the ḪURRI-Bird Oracle, the Snake Oracle, and the KIN Oracle. Although many studies have already explained how the different divination systems worked, the KIN oracle frame still remains difficult to understand in all of its features. In this research the KIN cuneiform sources and its oracular structure have been analyzed in all respects and enriched with tables, patterns, and pictures in order to better understand the work carried out. As far as the KIN is concerned, this research provides several different analytic implications both for Hittite and divination studies.